Ultra-high-Q resonances in plasmonic metasurfaces - M. Saad Bin-Alam (Nature Portfolio, 2021)
Metallic nanostructures are useful in many optical devices due to their nonlinear properties and responses to interaction with light. Here the authors demonstrate a metasurface of gold nanoparticle arrays with ultra-narrow surface lattice resonances of high quality-factor that operates in the telecommunication band.